2007
DOI: 10.1007/s00192-007-0455-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mode of delivery on pelvic floor functional anatomy

Abstract: The objective of this study is to investigate and compare the effects of different modes of delivery on urethral sphincter volume, bladder neck mobility, and changes to levator hiatus distensibility using ultrasound imaging. This study is a prospective observational cohort study. The setting of this study is at a London teaching hospital. The population is composed of 156 women recruited in their first ongoing pregnancy. Primigravid women were recruited between 32 weeks and term. Antenatal ultrasound measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
59
1
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 27 publications
8
59
1
4
Order By: Relevance
“…This downward traction might also cause more supportive system damage and hypermobility of the urethra. The same effect has been described after vaginal delivery compared to caesarean section [21,22] .…”
Section: Discussionsupporting
confidence: 62%
“…This downward traction might also cause more supportive system damage and hypermobility of the urethra. The same effect has been described after vaginal delivery compared to caesarean section [21,22] .…”
Section: Discussionsupporting
confidence: 62%
“…Several studies evaluated the bladder-neck mobility using ultrasound after the first delivery. 23 They showed that bladder-neck mobility was increased after vaginal delivery and unchanged after cesarean. Fritel et al, in their study showed that cesarean was significantly associated with a lower risk of SUI compared to normal delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies indicate that women with stress urinary incontinence and bladder neck mobility have lower pelvic floor muscle strength 14,27 . Others indicate that vaginal delivery is correlated with larger levator hiatus diameter and greater bladder neck mobility 28 . It is plausible to suggest that these women may have less pelvic floor muscle strength.…”
Section: Discussionmentioning
confidence: 99%